Characteristics of human immunodeficiency virus infection/acquired immune deficiency syndrome patients with pulmonary tuberculosis co-infection in Yowari Regional General Hospital of Jayapura - Rumainum, Greace (International Journal of Research in Medical Sciences, 2023)
Background: Pulmonary tuberculosis (TB) is an opportunistic co-infection on patients with human immune-deficiency virus (HIV) infection. The risk of pulmonary TB significantly increases with an HIV infection. This study aims to determine the characteristics of patients with TB-HIV co-infection receiving treatment in Yowari Regional General Hospital, Jayapura from July to December 2022. Methods: This is an observational descriptive study with cross-sectional design, using information of samples obtained from the medical records. Total sampling technique was used for this study. Results: All patients with TB-HIV co-infection are used as samples for this study, with the total of 24 samples. In this study, 58% of the samples were men, 79% death occurred within the age group of 20-40 years old, 83% employed, 58% has finished high school, and 67% had normal body mass index (BMI) level. Conclusions: Patients with TB-HIV co-infection in Yowari Regional General Hospital, Jayapura is mostly dominated with men, age of 20-40 years old, employed, has finished high school, and had normal BMI level.